Au Extraction from Mineral Rocks with Aeration-Cyanidation Hydrometallurgy and Comparative Study of Its Effectiveness in Various Methods and Solvents - Dhita Ariyanti; Muhammad Syaifuddin (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
Indonesia is a country with abundant mining potential, one of it is gold (Au) which has a high economic value. Separation of gold metal from mineral rock consists of several methods, such as extraction, hydrometallurgy, and membrane emulsifier technology. These three methods produce different effectiveness of percentage recovery (%recovery), depend on the optimum conditions of each method and type of solvent. This study aims to separate the gold metal from mineral rocks through the hydrometallurgical method with an aeration-cyanidation solvent combination. Hidrometallurgy method is liquid extraction from ores. The test used is a qualitative test of SnCl2 solution and characterization test with XRF. The results showed that the percentage of recovery (%recovery) of Au with aeration and cyanidation process for 24 hours was 92.8%. Aeration and cyanidation better than emulsifier membrane method and hydrometallurgy with sodium bisulphite, hydrogen peroxide, Cyanex 272 and NH4Cl 0.9 M.